A Real-time Internet of Things-Based Wireless Livestock Tracking System for Theft Prevention - Sandlana, Muzi; Mathonsi, Topside E.; Deon du Plessis; Tu, Chunling (AI Society & STMIK Indonesia, 2025)
Livestock theft is a significant threat to the agricultural industry, necessitating innovative preventive strategies. This study proposes a Wireless Livestock Tracking System (WLTS) that uses real-time Internet of Things (IoT) technologies to prevent livestock theft. The WLTS integrates GPS sensors with Long Range Radio (LoRa) wireless communication modules, overcoming the limitations of Wi-Fi and Bluetooth-based systems. It uses a single LoRa network receiver to facilitate real-time communication between farmers and their livestock. Simulation results show the WLTS effectively mitigates livestock theft, enabling farmers to quickly identify and recover stolen animals. Geofencing alerts enhance the system's sensitivity to potential theft scenarios. The WLTS has a user-friendly interface, allowing farmers to remotely monitor their livestock. Data analytics capabilities enable predictive analysis of probable theft trends based on historical data. The findings pave the way for practical implementation, revolutionizing livestock protection and safeguarding farmers' livelihoods worldwide.